Filmowy Mińsk (1915–1918) – polskie doświadczenie podczas Wielkiej Wojny - Guzek , Mariusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Polish film life in the Eastern Borderlands of the former Republic of Poland is replete with numerous white spots. During World War One, however, activity was quite intense, as evidenced by book-length studies on Vilnius, Lviv and even Kiev. Minsk, the future capital of Belarus, also had its own film-related Polish culture. The article focuses on the functioning of Minsk cinemas and their repertoire, as well as the Polish accents associated with them, which repeatedly had a mobilizing and identitarian character around which the national community of this provincial city was organized. Minsk’s border status means its cinematographic ancestry can be claimed by various national cinematographies, including Russian and Belarusian, but the source query and resulting findings clearly indicate that in the years of the Great War, this center was most strongly associated with Polish culture